The effect of dietary nitrate and vitamin C on endothelial function, oxidative stress and blood lipids in untreated hypercholesterolemic subjects: A randomized double-blind crossover study - Basaqr, Reem; Skleres, Michealia; Jayswal, Rani; Thomas, D. Travis (Clinical nutrition (Edinburgh, Scotland), 2021)
Vitamin C may enhance nitric oxide (NO) production through stepwise reduction of dietary nitrate (NO3) to nitrite (NO2) to NO. The combined effect of vitamin C and NO3 supplementation is relatively unexplored in untreated hypercholesterolemia. We aimed to examine whether co-administration of vitamin C and nitrate for 4-weeks would improve endothelial function (primary outcome), plasma NO metabolites, oxidative stress, and blood lipids (secondary outcomes). Subjects 50–70 years of age with low density lipoprotein (LDL) > 130 mg/dL and RHI ≤2 were enrolled in this randomized double-blind crossover study. Subjects were assigned to two 4-week supplementation treatments starting with 70 ml of concentrated beetroot juice (CBJ) with 1000 mg of vitamin C (NC) or CBJ with matched placebo (N), then switched to alternate treatment following 2-week washout. The change in reactive hyperemia index (RHI), sum of plasma NO metabolites (NO2 + NO3 (NOx)), oxidized LDL (oxLDL), and serum lipids were assessed at baseline and at 4-weeks of each treatment period. Eighteen subjects (11M:7F) completed all study visits. No significant treatment differences were observed in RHI change (N: 0.21 ± 0.12; NC: 0.20 ± 0.17; p = 0.99). Secondary analysis revealed that a subgroup of NC subjects who started with a baseline RHI of <1.67 (threshold value for ED) had greater improvements in RHI compared to subjects with RHI >1.67 (1.23 ± 0.15 to 1.96 ± 0.19; n = 8 vs. 1.75 ± 0.11 to 1.43 ± 0.10; n = 8; p = 0.02). Compared to N, NC experienced a significant increase in plasma NOx (N: 94.2 ± 15.5 μmol/L; NC: 128.7 ± 29.1 μmol/L; p = 0.01). Although there was no significant difference in oxLDL change between treatments (N: −1.08 ± 9.8 U/L; NC: −6.07 ± 9.14 U/L; p = 0.19), NC elicited significant reductions in LDL (N: 2.2 ± 2; NC: −10.7 ± 23; p = 0.049), triglycerides (N: 14.6 ± 43; NC: −43.7 ± 45; p = 0.03), and no change in serum high density lipoprotein. Within treatment group comparisons showed that only NC reduced oxLDL significantly from baseline to 4 weeks (p = 0.01). No between intervention differences were observed in RHI. RHI only improved in NC subjects with ED at intervention baseline. Four weeks of NC enriched the NO pool and promoted reduction of blood lipids and oxidative stress in subjects with hypercholesterolemia. These preliminary findings highlight a supplementation strategy that may reduce the progression of atherosclerotic disease and deserves further attention in studies using flow mediated dilation methods. www.clinicaltrials.gov (NCT04283630).